Precarious attachments: soldiers and erasures of the feminine in the Pakistan military. Issue 4 (8th August 2022) - Rashid, Maria
ABSTRACT: Militarism and soldiering are materialized by gendered imaginaries and enabled through physical and emotional labor within military households. Soldier households in Pakistan are rarely nuclear, and soldiering in the Pakistan military is filtered through the structures of rurality, postcoloniality, and localized manifestations of patriarchy. This article draws upon interviews, ethnographic fieldwork, and participant observation in villages in Pakistan and institutions of the military to examine the emotional labor in relationships between soldiers and their female kin, wives, and mothers. The silences and disconnects experienced in these relationships are not a side effect of soldiering and its demands; on the contrary, they need to be understood as the essence of the processes that create soldier-subjects. These attachments and enablers of soldiering are also, paradoxically, premised on ideas of precariousness, a disjuncture that can be better understood through the prism of the military institution's complicated relationship with the female subject – a relationship built on (dis)enchantment with the feminine (other). This article sets up these erasures of connection, the enabling yet fragile relationships between the soldier and his female kin, as intimate sites to understand militarism. These relationships both sustain the war project and hold the potential for diminishing it.